Addressing Law Enforcement Issues in ASEAN Mutual Legal Assistance (MLA) Regime Towards Transnational Organised Crime: Lessons from Illicit Drugs Case in ASEAN - Rafiqo Fadhlullah (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Transnational organised crime in Southeast Asia, particularly illicit drug trafficking, continues to escalate despite ASEAN cooperation frameworks. Although mechanisms such as the ASEAN Ministerial Meeting on Transnational Crime and the Mutual Legal Assistance Treaty (MLAT) exist, law-enforcement coordination remains weak, resulting in ineffective cross-border investigation and prosecution. Previous studies discuss ASEAN security cooperation but have not adequately examined how institutional capacity, compliance gaps, and divergent legal systems constrain the effectiveness of MLA. Moreover, Regime Theory has not been used to evaluate MLA in illicit-drug cases, leaving an analytical gap regarding its structural and functional limitations.This article offers a novel contribution by integrating Regime Theory with regional institutionalism to evaluate ASEAN’s MLA regime through the dimensions of problem structure, institutional capacity, resource availability, and compliance mechanisms. The objective of this study is to assess why ASEAN’s MLA framework needs to be expanded and deepened to resolve persistent law-enforcement challenges in countering transnational organised crime, particularly illicit drugs. This research employs a qualitative method using primary ASEAN legal documents, treaty instruments, and secondary scholarly analyses. The findings show that ASEAN’s MLA regime remains constrained by fragmented legal harmonisation, weak compliance enforcement, insufficient institutional capacity, and unequal resources among member states. These weaknesses hinder evidence sharing, delay cross-border investigations, and produce inconsistent prosecutorial outcomes. The study concludes that strengthening MLA requires deeper harmonisation of procedural rules, enhanced institutional coordination, capacity-building initiatives, and future development of a region-wide extradition mechanism.